Modeling unobserved heterogeneity using person-centered approaches: Latent profiles of preservice teachers' emotional awareness - Sozer-Boz, Esra; Akbas, Derya; Kahraman, Nilufer (Izzet Kara, 2023)
Latent Class and Latent Profile Models are widely used in psychological assessment settings, especially when individual differences are suspected to be related to unobserved class memberships, such as different personality types. This paper provides an easy-to-follow introduction and application of the methodology to the data collected as part of more extensive educational research investigating social-emotional competency profiles of preservice teachers (n=184) who responded to an Emotional Awareness Questionnaire. Suspected that there would be two or more latent emotional awareness sub-groups in the sample, a series of latent profile models was estimated. The results suggested three distinct emotional awareness profiles; namely, introverted, extroverted, and less sensitive to others' emotions, with proportions of 9%, 56%, and 35%, respectively. Subsequent analyses showed that preservice teachers with higher levels of emotionality, sociability, and well-being were more likely to be in the extroverted profile. The findings suggest that nearly half of the teachers in the sample could be expected to possess the most professionally desirable teacher profile. Nonetheless, it was noted that if timely diagnostic and tailored training or intervention programs were available, at least some of the preservice teachers in the less sensitive to others' profiles, and most of the preservice teachers in the introverted profile could be helped to self-observe the way which they tend to identify and regulate their emotions.
Modeling unobserved heterogeneity using person-centered approaches: Latent profiles of preservice teachers' emotional awareness
Keywords: Latent Profile; Heterogeneity; Preservice Teachers; Emotional Awareness